2016
DOI: 10.1080/10580530.2016.1155948
|View full text |Cite
|
Sign up to set email alerts
|

Citizen Adoption of E-Government Services: Exploring Citizen Perceptions of Online Services in the United States and United Kingdom

Abstract: Her research interests include technology adoption, e-government and cyber security. She has published in several top-tier journals, including the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
108
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(117 citation statements)
references
References 112 publications
(162 reference statements)
6
108
1
2
Order By: Relevance
“…I believe that Digital currency would act in my best interest. (Bélanger & Carter, 2008;Carter, Weerakkody, Phillips, & Dwivedi, 2016;Shahzad et al, 2018) I expect information about Digital currency financial system is sincere.…”
Section: Appendix Constructmentioning
confidence: 99%
“…I believe that Digital currency would act in my best interest. (Bélanger & Carter, 2008;Carter, Weerakkody, Phillips, & Dwivedi, 2016;Shahzad et al, 2018) I expect information about Digital currency financial system is sincere.…”
Section: Appendix Constructmentioning
confidence: 99%
“…A number of scholars have equally reported that the easiness that is associated with IS/IT based services such as social networking (Wamba, et al, 2017), e-government (Carter et al, 2016;Susanto & Aljoza, 2015), e-insurance (Leeet al, 2015) and mobile banking (Safeena et al, 2011) is a core determinant of adoption of these latest technology trends. The essence of these findings indicate that the absence of face-to-face interaction that is common in an internet enabled services platforms such as mobile commerce requires such platform to be easily used with regards to user friendliness as this will reduce the difficulty that may be associated with the usage of the services (Chong et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Especially, citizens' trust in the government agencies' capability of providing secure e-services is vitally important for e-government adoption (Carter, Weerakkody, Phillips, & Dwivedi, 2016). Existent literature provides accumulated empirical evidences that trust in technology foster acceptance or continued acceptance of various technologies such as online banking service (Lin, 2011), supply chain information systems (Lippert, 2007), recommender system (Wang & Benbasat, 2005), e-commerce (Corbitt, Thanasankit, & Yi, 2003), and e-government services (Bélanger & Carter, 2008;Carter et al, 2016). More specifically, as trust in the form of human-like trust and system-like trust, portray user's wholistic belief in egovernment service, we hypothesize that: H7a Human-like trust will positively affect Continuance Intention.…”
Section: Trust and Continuance Intentionmentioning
confidence: 99%